DAMP molecules S100A9 and S100A8 activated by IL‐17A and house‐dust mites are increased in atopic dermatitis. Issue 12 (December 2014) - Jin, Shan; Park, Chang Ook; Shin, Jung U; Noh, Ji Yeon; Lee, Yun Sun; Lee, Na Ra; Kim, Hye Ran; Noh, Seongmin; Lee, Young; Lee, Jeung‑Hoon; Lee, Kwang Hoon
Abstract S100A9 and S100A8 are called damage‐associated molecular pattern (DAMP) molecules because of their pro‐inflammatory properties. Few studies have evaluated S100A9 and S100A8 function as DAMP molecules in atopic dermatitis (AD). We investigated how house‐dust mites affect S100A9 and S100A8 expression in Th2 cytokine‐ and Th17 cytokine‐treated keratinocytes, and how secretion of these molecules affects keratinocyte‐derived cytokines. Finally, we evaluated expression of these DAMP molecules in AD patients. S100A9 expression and S100A8 expression were strongly induced in IL‐17A‐ and Dermatophagoides (D.) farinae‐treated keratinocytes, respectively. Furthermore, co‐treatment with D. farinae and IL‐17A strongly increased expression of S100A9 and S100A8 compared with D. farinae‐Th2 cytokine co‐treatment. The IL‐33 mRNA level increased in a dose‐dependent manner in S100A9‐treated keratinocytes, but TSLP expression did not change. S100A8/A9 levels were also higher in the lesional skin and serum of AD patients, and correlated with disease severity. Taken together, S100A9 and S100A8 may be involved in inducing DAMP‐mediated inflammation in AD triggered by IL‐17A and house‐dust mites.